ANALISA PENGARUH VARIASI BENTUK ABSORBER PADA ALAT DESTILASI AIR LAUT TERHADAP KENAIKAN SUHU AIR DALAM RUANG PEMANAS DAN JUMLAH PENGUAPAN AIR YANG DIHASILKAN - Mukaddim, Aldi; Wirawan, Made; Alit, Ida Bagus (Universitas Mataram, 2013)
Clean water is a requirements of very important human life. Indonesia is a maritime country that has many islands surrounded by ocean, had a decreased clean water problem. One of the method to be used for obtain clean water is sea water distillation process. One of the most important tools is absorber distillation. occurs heat transfer from the absorber to the sea water causing, rising sea temperatures cause sea water to evaporate. The rising temperature of the sea water increases the amount of evaporation that occurs. The more the amount of evaporation generated will increase the number of fresh water produced. Increased seawater temperatures by increasing the temperature absorber, so it needs to be analyzed shape of the absorber which one can be produce more clean water than the others, a conclusion of the study indicated that solar distillation plat shape with a huge wave absorber produces more clean water than the others , the average amount of water that is more of 908 ml, compared with a small wave absorber plate only produce 764.4 ml average a day and a flat plate absorber only produce 599 ml average a day, it is not independent of heat absorption by absorber, solar distillation plat shape with a huge wave absorber absorbs more heat than the other two absorber plates, this has resulted in solar distillation shape with a huge wave absorber plate very well produce more water than the otehrs.